Autonomous active power control for an islanded AC microgrid using improved bus signaling method. (December 2019) - Sorouri, M.; Shakarami, M.R.; Soltani, J.
Highlights: Autonomous active power control by the improved bus-signaling method. Active power control of an AC microgrid without using secondary frequency control. Elimination of frequency deviation in an AC microgrid by the proposed method. Protecting batteries against unsafe condition over-charging and over-discharging. Abstract: In an islanded AC microgrid, consists of distributed energy storage systems (ESSs), photovoltaics (PVs) and loads, coordinated active power control is necessary for the effective operation of the components. Also, protecting the ESSs against damaging conditions of over-charge and over-discharging, along with active power control is very important. For this purpose, a lot of centralized and decentralized methods have been proposed. One of the decentralized methods is the frequency bus-signaling method (FBSM). The weakness of this method is the frequency deviation after power balancing. This problem is generally solved by a secondary control that relies on communication links between inverters. In this paper, an improved FBSM is proposed in which frequency deviation is eliminated without the use of communication links. The proposed method is based on two algorithms. The first algorithm is for microgrid frequency control (MFC). This algorithm adjusts the frequency according to the threshold and state of charge ( SoC ) slope. The second algorithm is for the PV power control (PVPC) to adjust the produced power of the PV systems according to the slope and threshold of measured frequency. The simulation results, under different radiations and the SoC conditions, show the effectiveness of the proposed method.